Validation of Online Versions of Tinnitus Questionnaires Translated into Swedish - Müller, Karolina; Edvall, Niklas K.; Idrizbegovic, Esma; Huhn, Robert; Cima, Rilana; Persson, Viktor; Leineweber, Constanze; Westerlund, Hugo; Langguth, Berthold; Schlee, Winfried; Canlon, Barbara; Cederroth, Christopher R. (Frontiers in Aging Neuroscience, 2016)
Background Due to the lack of objective measures for assessing tinnitus, its clinical evaluation largely relies on the use of questionnaires and psychoacoustic tests. A global assessment of tinnitus burden would largely benefit from holistic approaches that not only incorporate measures of tinnitus but also take into account associated fears, emotional aspects (stress, anxiety, and depression), and quality of life. In Sweden, only a few instruments are available for assessing tinnitus, and the existing tools lack validation. Therefore, we translated a set of questionnaires into Swedish and evaluated their reliability and validity in a group of tinnitus subjects. Methods We translated the English versions of the Tinnitus Functional Index (TFI), the Fear of Tinnitus Questionnaire (FTQ), the Tinnitus Catastrophizing Scale (TCS), the Perceived Stress Questionnaire (PSQ-30), and the Tinnitus Sample Case History Questionnaire (TSCHQ) into Swedish. These translations were delivered via the internet with the already existing Swedish versions of the Tinnitus Handicap Inventory (THI), the Hospital Anxiety and Depression Scale (HADS), the Hyperacusis Questionnaire (HQ), and the World Health Organization Quality of Life questionnaire (WHOQoL-BREF). Psychometric properties were evaluated by means of internal consistency (Cronbach’s alpha [α]) and test-retest reliability across a 9-week interval (Intraclass Correlation Coefficient [ICC], Cohen’s kappa) in order to establish construct as well as clinical validity using a sample of 260 subjects from a population-based cohort. Results Internal consistency was acceptable for all questionnaires (α >0.7) with the exception of the ‘social relationships’ subscale of the WHOQoL-BREF. Test-retest reliability was generally acceptable (ICC >.70, Cohens Kappa >.60) for the tinnitus-related questionnaires, except for the TFI ‘sense of control’ subscale and 15 items of the TSCHQ. Spearmen rank correlations showed that almost all questionnaires on tinnitus are significantly related, indicating that these questionnaires measure different aspects of the same construct. The data supported good clinical validity of the tinnitus-related questionnaires. Conclusion Our results suggest that most Swedish adaptations of the questionnaires are suitable for clinical and research settings and should facilitate the assessment of treatment outcomes using a more holistic approach by including measures of tinnitus fears, emotional burden, and quality of life.